ANALISIS VARIASI BAHASA AKRAB DALAM PERISTIWA ALIH KODE DI LINGKUNGAN PANTI ASUHAN PUTRI ‘AISYIYAH DAU - Novitasari; Sudjalil (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
The purpose of this study is to describe the use of various familiar languages ​​in code switching events in the Putri 'Aisyiyah Dau Orphanage. This research is a qualitative research. The approach used in this research is a descriptive approach. The source of the research data is in the form of conversations between students and students, students with caregivers, and caregivers with caregivers in private audio recordings in the Putri 'Aisyiyah Dau Orphanage. The data in this study are excerpts from conversations between students and students, students with caregivers, and caregivers with caregivers that contain variations of familiar language and code switching models. The data collection techniques in this study were: 1) Recording conversations in the Putri 'Aisyiyah Dau Orphanage, 2) Making transcriptions of data from conversations in the Putri 'Aisyiyah Dau Orphanage, 3) Grouping the findings according to indicators. The results of this study indicate: 1) The linguistic characteristics of the familiar language in the Putri 'Aisyiyah Dau Orphanage, 2) The factors that influence the code-switching event in the Putri' Aisyiyah Dau Orphanage, 3) The forms of code-switching in the environment Putri ‘Aisyiyah Dau Orphanage